Model Pengembangan Manajemen Bisnis Pondok Modern Darussalam Gontor Ponorogo, Indonesia - Suharto Suharto; Muhammad Iqbal Fasa (Institut Agama Islam Negeri Kendari, 2018)
This paper tries to offer business development model Pondok Modern DarussalamGontor Ponorogo Indonesia. Pondok Modern Darussalam Gontor success in managing30 business units formed its own characteristic. As for the characteristics of thebusiness unit management Pondok Modern Darussalam Gontor is: Planning based onthe value of cottage; Organizing based on regeneration; Transformative collectiveleadership; and Total Quality Control. In the implementation process, the characteristics of the management of the general shape characteristics, namely:Implementation Business Unit Based Learning By Doing; Implementation of SelfBerdruing System; Centralized Financial centralization; as well as the creation ofbalance and Baatinites lahiriyah Welfare.